Synthesis and evaluation of hydrophobically modified fenugreek gum for potential hepatic drug delivery - Minghui Zhou; Boli Li; Xinhui Zhang; Shaolong He; Yanni Ma; Wenping Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The objective of this study was to hydrophobically modify fenugreek gum (FG) and to further evaluate the potential application of the obtained derivative in liver-targeted drug delivery system. Stearic acid (C18) was conjugated with FG (FG-C18) by a simple esterification reaction. The obtained FG-C18 was then characterized on its chemical structure by Fourier transform infrared spectroscopy and 1H-nuclear magnetic resonance. The self-assembled nanomicelles (NMs) of FG-C18 in water were prepared by an ultrasonication method. The average diameter and zeta potential of FG-C18 NMs were 196.70 ± 6.12 nm and −31.79 ± 1.58 mV, respectively. FG-C18 NMs appeared as spherical particles under transmission electron microscopy and possessed a critical micellar concentration of 0.042 mg/ml by pyrene fluorescence probe method. A low toxicity of FG-C18 was revealed on both HepG2 and MCF-7 cells at 0.1–100 mg/ml. Haemolysis of FG-C18 was less than 5%. Cellular uptake of coumarin-6 into HepG2 cells was enhanced by treating with C6-loaded FG-C18 NMs compared to free coumarin-6. These results suggest that FG-C18 have a potential application for a liver targeted drug delivery.